Meru eProperties - Towett,Eutychus (Meru U: Eutychus Towett, 2013)
At some stage in our lives, most of us will need to look for a new home. Perhaps because of a new job, a change in family circumstances or accommodation requirements, we change and look foe a new place to live. Some people will want to start business in new places or to expand their offices there. When looking for a new home, some of them have specific areas in mind like somewhere close to schools , major roads or a railway station,in an area where costs are lower, urban areas, close to shops and their place of work.The task of looking for such a place can be a time consuming and frustrating. In addition looking for new properties to buy such as plots and land is a hard task.In order to solve these questions in finding a home acceptable to all family at right place at right cost, and to find properties, there is need for a system that will have the ability to provide those in need with the necessary information to find a suitable home or a property that will suit their needs.These customers will need to supply their requirements that will decide the place such as factors as the cost of the premise,proximity to school, railways and roads. The concept if this project is to have a web-based applications that will help those in the real estate industry and interact together and satisfy each other's needs. This system will give the property owners and the agents a platform where they can reach their customers easily and on the other hand, give the customers a place where they can find the property of their choice with ease.
A project submitted in partial fulfillment of the requirements for the degree in Bsc. Computer Technology